Microstructure and Mechanical Properties of Ultrafine-Grained Dual-Phase 0.1C3Mn Steel Processed by Warm Deformation - Yongkang Wang; Chenglu Liu; Qingquan Lai (Metals)
In this study, we have explored the thermomechanical processing on 0.1C3Mn steel to produce an ultrafine-grained (UFG) dual-phase (DP) microstructure. The composition was designed to allow a decrease in temperature for the warm deformation of austenite. It was found that the warm deformation of austenite induced a dramatic ferrite transformation, in contrast to the absence of the formation of ferrite in the well-annealed state. Compression by 60% at 650 °C resulted in the generation of a UFG-DP microstructure with a ferrite grain size of 1.4 μm and a ferrite volume fraction of 62%. The UFG-DP 0.1C3Mn steel presents a good combination of strength, ductility and fracture resistance, and the fracture strain of the UFG-DP is higher than the as-quenched low-carbon martensite. The high fracture strain of the UFG-DP could be attributed to delayed void nucleation and constrained void growth, as revealed by the quantitative X-ray tomography.